2011
DOI: 10.1007/s00775-011-0864-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying reductant-induced reactive oxygen species formation by anticancer copper(II) compounds

Abstract: Intracellular generation of reactive oxygen species (ROS) via thiol-mediated reduction of copper(II) to copper(I) has been assumed as the major mechanism underlying the anticancer activity of copper(II) complexes. The aim of this study was to compare the anticancer potential of copper(II) complexes of Triapine (3-aminopyridine-2-carboxaldehyde thiosemicarbazone; currently in phase II clinical trials) and its terminally dimethylated derivative with that of 2-formylpyridine thiosemicarbazone and that of 2,2'-bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 53 publications
8
94
0
2
Order By: Relevance
“…However, NAC pre-loading has instead been associated with protective effects against ROS generating copper complexes [24]. In our study, pre-incubation with NAC reduced the cytotoxic activity of VLX60 and therefore the interpretation is that a theoretically expected enhanced cytotoxic activity induced by a reduction of the copper complex extracellularly is outweighed by the antioxidant properties of NAC intracellularly.…”
Section: Discussionmentioning
confidence: 59%
“…However, NAC pre-loading has instead been associated with protective effects against ROS generating copper complexes [24]. In our study, pre-incubation with NAC reduced the cytotoxic activity of VLX60 and therefore the interpretation is that a theoretically expected enhanced cytotoxic activity induced by a reduction of the copper complex extracellularly is outweighed by the antioxidant properties of NAC intracellularly.…”
Section: Discussionmentioning
confidence: 59%
“…The UPR can be triggered by a wide variety of causes, including accumulation of misfolded/ unfolded proteins, imbalances in ER lipids and glycolipids, changes in the redox environment of the ER caused by ROS, and disruption of Ca 21 homeostasis. Recent studies showed that Cu 21 thiosemicarbazone complexes generate oxidative stress in cell-based assays, whereas the metal-free compounds do not (Hancock et al, 2011;Lovejoy et al, 2011;Kowol et al, 2012). Furthermore, the Cu 21 complex of the thiosemicarbazone NSC 689534 [2-pyridinecarbaldehyde N,N-bis(2-pyridinylmethyl) thiosemicarbazone] was shown to induce ER stress in a ROSdependent manner, whereas the metal-free NSC 689534 does not induce oxidative or ER stress (Hancock et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Fe and Cu complexes have long been predicted as biologically active forms due to intracellular redox cycling potential, and the efforts of synthesizing preformed complexes with Fe, Cu or other metal ions have been pursued in an attempt to improve therapeutic efficacy [5,2123]. In this study, we have discovered that the simple addition of Cu 2+ to the culture medium abrogates the cytotoxicity of triapine and PT in a 1:1 stoichiometric manner.…”
Section: Introductionmentioning
confidence: 87%